PELATIHAN PENGOLAHAN IKAN SORI MENJADI PRODUK BAKSO IKAN DI DESA TALLU BANUA, MAJENE, SULAWESI BARAT - Muhammad Nur; Tenriware Tenriware; Husniah Husniah; Adiara Firdhita Alam Nasyrah; Muhammad Said (Jurnal Abdi Insani, 2023)
Tallua Banua Village is one of the coastal villages where the majority of the population working as fisherman. One of the highlights in Tallu Banua Village is the catch majority of fisherman namely sori fish (Trisoluris sp.). The potential of sori fish is very large, especially when sori fish is abundant during the catch season, hence it is very suitable to be developed as a raw material for making various fishery products including fish balls. The main aims of this community service activity is to provide the training for business groups to get skills and knowledge about business management based on household-scale and diversification of sori fish processing products, hence this can increase their income and welfare. This activity was carried out on Sunday, 19 June 2023 at the Beach Fish Seed Hall, Tallu Banua Village. The training participants in this PKM were the fisherman women’s groups of Tallu Banua Village. The method used is to provide material and direct practice of making fishball products. The results of this service activity show an increase in community knowledge related to procedures for carrying out a good and correct fish processing production by paying attention to SOP (Standard Operating Procedure) and SSOP (Standard Sanitation Operational Procedure), carrying out good business management including raw material management and production supporting materials, workforce management and business group financial bookkeeping as well as marketing strategy. Furthermore, with this activity the community group also gained skills in processing sori fish into value-added products, namely making sori fish meatballs starting from weeding, washing, mixing spices, boiling, to packaging. This training is very useful for fishermen women's groups in an effort to increase their income and welfare through training in processing sori fish into fish meatball products.